Hair zinc level and autism spectrum disorder in children - Windiani, I Gusti Ayu Trisna; Adnyana, I Gusti Agung Ngurah Sugitha; Pratiwi, Ni Luh Putu Sukma; Hapsari, Ida Ayu Nyoman Dian Permana (Paediatrica Indonesiana, 2024)
Background Autism spectrum disorder (ASD) is one of the most common neurodevelopmental disorders. In children with ASD, the neurodevelopmental and behavioral disorders are characterized by impaired quality of interaction, communication, and social imagination, with limited interest and repetitive behavior. Various studies have found that the mean zinc level is lower in children with ASD than in children without ASD, especially in the low functioning autism. Objective To compare hair zinc level in children with and without ASD. Methods This case-control study included children with ASD and controls without ASD. Subjects were children under 5 years old who came to Prof I.G.N.G. Ngoerah Hospital and Masadini Clinic in Denpasar. Hair zinc cut-off level was determined by the area under curve (AUC) based on the receiver operating characteristic (ROC) curve. Results A total of 128 subjects consisted of 64 cases and 64 controls, with a mean age of 4 (SD 0.8) years. Most subjects were male (76%); 82.3% were well-nourished. The mean maternal age at delivery was 28.82 (SD 3.2) years. Subjects’ mean hair zinc level was 87.9 (SD 231.1) ?g/g. Bivariate analysis with Chi-square test revealed that children with hair zinc concentration of <33.88 ?g/g were 22.19 times more likely to have ASD than those with higher zinc levels (OR 22.19; 95%CI 8.02 to 42.09; P<0.001). Conclusion Low hair zinc level is more likely to occur in children with ASD than in children without ASD.